Treatment in the pediatric emergency department is evidence based: a retrospective analysis - Hartling Lisa; Cramer Kristie; Wiebe Natasha; Waters Kellie L; Klassen Terry P (BMC, 2006)
Abstract Background Our goal was to quantify the evidence that is available to the physicians of a pediatric emergency department (PED) in making treatment decisions. Further, we wished to ascertain what percentage of evidence for treatment provided in the PED comes from pediatric studies. Methods We conducted a retrospective chart review of randomly selected patients seen in the PED between January 1 and December 31, 2002. The principal investigator identified a primary diagnosis and primary intervention for each chart. A thorough literature search was then undertaken with respect to the primary intervention. If a randomized control trial (RCT) or a systematic review was found, the intervention was classified as level I evidence. If no RCT was found, the intervention was assessed by an expert committee who determined its appropriateness based on face validity (RCTs were unanimously judged to be both unnecessary and, if a placebo would have been involved, unethical). These interventions were classified as level II evidence. Interventions that did not fall into either above category were classified as level III evidence. Results Two hundred and sixty-two patient charts were reviewed. Of these, 35.9% did not receive a primary intervention. Of the 168 interventions assessed, 80.4% were evidence-based (level I), 7.1% had face validity (level II) and 12.5% had no supporting evidence (level III). Of the evidence-based interventions, 83.7% were supported by studies with mostly pediatric patients. Conclusion Our study demonstrates that a substantial proportion of PED treatment decisions are evidence-based, with most based on studies in pediatric patients. Also, a large number of patients seen in the PED receive no intervention.